Methylation of Salmonella Typhimurium flagella promotes bacterial adhesion and host cell invasion - Julia A. Horstmann (Nature Portfolio, 2020)
Flagellin proteins of Salmonella flagella are methylated. Here, the authors show that flagellin methylation facilitates adhesion of Salmonella to hydrophobic host-cell surfaces, and contributes to efficient gut colonization and host infection.